Switching from Deferasirox Dispersible Tablets to Deferasirox Film-Coated Tablets: Is There an Effect on Ferritin Levels in Children and Adolescents with Transfusion-Dependent Anemia? - Esra Arslantaş; Ali Ayçiçek; Sibel Akpınar Tekgündüz; Duygu Özkorucu Yıldırgan; Ayşe Özkan Karagenç; Tuba Nur Tahtakesen Güçer; Ayşe Gonca Kaçar; Cengiz Bayram; Nihal Özdemir (AVES Yayincilik, 2024)
Objective: To investigate the effect of switching from deferasirox dispersible tablet (DT) to deferasirox film-coated tablet (FCT) on serum ferritin (SF) levels in transfusion-dependent patients. Materials and Methods: Patients who received regular erythrocyte transfusion and whose treatment was switched from DT to FCT were included in the study. FCT start date was taken as the index date. Patients were followed over 2 equal and long periods, both before and after index date. Results: Thirty-two patients were included, and the comparison periods ranged from 4 to 12 months. The SF values increased from a median of 1723 ng/mL (range 717-5369 ng/mL) to 1.853 ng/mL (range 924-5478 ng/mL) after switching from DT to FCT (P = .036). While there was a significant increase in median SF after switching in Turkish patients (1467 ng/mL to 1778 ng/ mL, P = .010) and patients ≥12 years (1598-1848 ng/mL, P = .009), there was an insignificant (P = .859) decrease in SF in immigrant children. Considering only the post-switch period, there was a non-significant increase in median SF in the entire cohort, while SF decreased significantly in immigrant children (P = .026). No serious side effects were observed in any patient that would cause discontinuation of treatment. Conclusion: Overall, higher SF value was observed with FCT compared to DT in short term. There were different results between patient groups. Our results suggest that FCT is more effective than DT in patients with high basal ferritin and who are actually incompatible with treatment and should be preferred first in these patients.